2021
DOI: 10.1002/jsfa.11272
|View full text |Cite
|
Sign up to set email alerts
|

Salinity differently affects antioxidant content and amino acid profile in two cultivars of Amaranthus cruentus differing in salinity tolerance

Abstract: BACKGROUND: Amaranthus cruentus is a promising leafy vegetable with high nutritional value and is able to cope with salt stress but the impact of sodium chloride (NaCl) on its main properties have not been studied in detail. Plants from two contrasting cultivars (Rouge: salt-tolerant and Locale: salt-sensitive) were exposed to NaCl (0, 30, 60 and 90 mmol L -1 ) in nutrient solution for 2 weeks. Plant growth, mineral content, oxidative status and antioxidant concentration, salicylic acid concentration, protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Our results showed that the salt response of A. cruentus may differ according to the NaCl concentration. A previous study on A. cruentus leaf cultivars found that a low concentration of NaCl in hydroponic conditions could stimulate several parameters related to mineral content and oxidative status [ 34 ]. After two weeks of exposure, 30 mM NaCl had a positive effect on the plant growth and health compared to control conditions, whereas higher concentrations (60 and 90 mM) had detrimental effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that the salt response of A. cruentus may differ according to the NaCl concentration. A previous study on A. cruentus leaf cultivars found that a low concentration of NaCl in hydroponic conditions could stimulate several parameters related to mineral content and oxidative status [ 34 ]. After two weeks of exposure, 30 mM NaCl had a positive effect on the plant growth and health compared to control conditions, whereas higher concentrations (60 and 90 mM) had detrimental effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on A. cruentus leaf cultivars found that a low concentration of NaCl in hydroponic conditions could stimulate several parameters related to mineral content and oxidative status [ 34 ]. After two weeks of exposure, 30 mM NaCl had a positive effect on the plant growth and health compared to control conditions, whereas higher concentrations (60 and 90 mM) had detrimental effects [ 34 ]. After 4 weeks of exposure to 50 and 100 mM NaCl, the results of the present experiment differed substantially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the role of genes PAL and TAL (encoding, tyrosine ammonia-lyase) has also been described in phenylpropanoid metabolism (Barros and Dixon 2020). Studies have reported the increased activities of these two genes under various biotic and abiotic stresses, leading to more metabolite accumulation (Lu et al 2016;Luyckx et al 2021;Nisar et al 2021;Sasi et al 2021). Along with these two genes, the role of STS has been specifically related to the accumulation of stilbenes, as a decline in the expression of STS decreases its biosynthesis (Jeandet et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Amaranthus spinosus seeds have moderate adaptabilities to salt concentrations among Amaranthus species. Salt resistance trends of Amaranthus palmeri seeds are similar to those of Amaranthus cruentus [33,54,55], stronger than those of Amaranthus retroflexus, Amaranthus blitoides, and Amaranthus albus, and weaker than those of Amaranthus tricolor and Amaranthus giganticus [33,35,36,56].…”
Section: Effects Of Different Salt Concentrations Onmentioning
confidence: 99%